Selection of probiotic candidate of lactic acid bacteria from Hermetia illucens larvae fed with different feeding substrates - DINI JULIA SARI SIREGAR; ELISA JULIANTI; MA’RUF TAFSIN; DWI SURYANTO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Siregar DJS, Julianti E, Tafsin M, Suryanto D. 2022. Selection of probiotic candidate of lactic acid bacteria from Hermetia illucens larvae fed with different feeding substrates. Biodiversitas 23: 6320-6326. Exploration of probiotics candidate have been accelerated from unique and novel source, one of which is from black soldier fly (Hermetia illucens). The black soldier flies are known as omnivores which are commonly reared, harvested and utilized to convert organic wastes into biomass yet reducing the amount of abundant waste in nature. Lactic acid bacteria (LAB) is one of beneficial gut symbionts which can be found across animal taxa, including insect, however, limited information is currently reported from H. illucens as a potential harboring insect. This study aimed to determine the probiotics candidate from the gut of H. illucens fed with different feeding substrates to improve the gut microbiota. The larvae were nourished with chicken manure, tofu solid wastes and vegetable wastes prior isolation of LAB. The LAB isolates were tested for their antagonistic activity against enteric pathogens, pH and bile salt tolerance, and adherence to chicken intestine (ileum). Based on the growth performance under physiological stresses and multivariate analysis using principal component analysis (PCA), four LAB isolates were designated as putative probiotics. The four isolates were Lactiplantibacillus. pentosus 5P2i1, Lacticaseibacillus. paracasei 5P2i5, Lactiplantibacillus. pentosus 5P2i9, and Lactiplantibacillus. plantarum 6P1i1 was then declared as novel strains that could be developed further as poultry probiotics.